“Eating Your Path”: Fairy Lore and Scarcity in Newfoundland and Labrador - Tye, Diane (Ethnologies, 2024)
My interest here is in how Newfoundlanders and Labradorians have used folklore, specifically fairy lore, to think about life lived in the context of a pervasive history of scarcity. Extending to fairy traditions Dorothy Noyes’s argument that oral folktales collected in the nineteenth century represent “a space of analysis and debate among poor people evaluating their life options” (Noyes 2016: 300), I ask how fairy lore in Newfoundland and Labrador allowed earlier residents to think about economic hardship and food insecurity.